Employer discrimination and the immutability of ethnic hierarchies: A field experiment - Kåre Vernby; Rafaela M. Dancygier (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2018)
How pervasive is labor market discrimination against immigrants and what options do policymakers and migrants have to reduce it? To answer these questions, we conducted a field experiment on employer discrimination in Sweden. Going beyond existing work, we test for a large range of applicant characteristics using a factorial design. We examine whether migrants can affect their employment chances - by adopting citizenship, acquiring work experience, or signaling religious practice - or whether fixed traits such as country of birth or gender are more consequential. We find no evidence that immigrants can affect their employment chances by any of the tested means. Rather, ethnic hierarchies are critical: callback rates decline precipitously with the degree of ethno-cultural distance, leaving Iraqis and Somalis, especially if they are male, with much reduced employment chances. These findings highlight that immigrants have few tools at their disposal to escape ethnic penalties and that efforts to reduce discrimination must address employer prejudice.
Keywords: J7; J23; 330; country of birth; citizenship; gender; work-experience; religion; discrimination; field experiment; labor market